PLANNED COMPLEX SUICIDE BY HANGING AND DROWNING IN A WATER DRUM INSCRIBED WITH SUICIDE NOTE (Journal of Forensic Medicine & Toxicology, 2022)
Hanging or drowning is combined with other method/s in planned and unplanned complex suicides. However, simultaneous use of any two methods of mechanical asphyxia is un-reported in planned complex suicide. Authors describe an unprecedented case of suicide of a 56-year-old man who was found dead inside a water drum. The drum was also utilized to be inscribed with suicide note, as well as a farewell message. Hanging being a surest method of death is usually exercised at last in complex suicides, but used as first method here. This is also the first case of planned complex suicide wherein hanging and drowning were used together. The intent of the deceased to safeguard via multiples measures against the faulty implication of family member/s to be held responsible for his death was really interesting. Inscription of suicide note has also never been reported over water drum, and is another highlight of this case.
Keywords: Planned complex suicide; Hanging; Drowning; Asphyxia; Water drum; Suicide note